Economic Growth and Human Development - Alejandro Ramirez; Gustav Ranis; Frances Stewart (Yale University, Economic Growth Center, 1997)
This paper explores the links between economic growth and human development, identifying two chains, one from economic growth to human development, the other, from human development to economic growth. The importance of various links in each chain are explored empirically with the help of cross-country statistics for the period 1970-92. Public expenditures on health and education, notably female, represent especially important links determining the strength of the relationship between economic growth and human development. The investment rate and income distribution are significant links determining the strength of the relationship running from development to economic growth. These two-way chains can generate self-reinforcing, virtuous or vicious cycles of development, as well as identifying lop-sided performers. Over time we find that lop-sided development seldom persists: countries initially in favor of economic growth lapse into the vicious category, while countries favoring human development advance into the virtuous category. This finding implies that, although both human development and economic growth should be jointly promoted, human development should be given sequential priority.
Keywords: O10; O11; O15; O57; 330; Human Development; Economic Growth; Cross-country Statistics 70-92; Resource Allocation; Income Distribution; Poverty; Productivity; Health; Technology; Education; Entwicklungskonvergenz; Welt